Effects of preconception care and periconception interventions on maternal nutritional status and birth outcomes in low‐ and middle‐income countries: A systematic review - Zohra S. Lassi; Sophie G. E. Kedzior; Wajeeha Tariq; Yamna Jadoon; Jai K. Das; Zulfiqar A. Bhutta (Campbell Systematic Reviews, 2021)
Abstract Background The preconception period is an ideal time to introduce interventions relating to nutrition and other lifestyle factors to ensure good pregnancy preparedness, and to promote health of mothers and babies. In adolescents, malnutrition and early pregnancy are the common challenges, particularly among those who live in low‐ and middle‐income countries (LMIC) where 99% of all maternal and newborn deaths occur. These girls receive little or no attention until their first pregnancy and often the interventions after pregnancy are too late to revert any detrimental health risks that may have occurred due to malnutrition and early pregnancy. Objectives To synthesise the evidence of the effectiveness of preconception care interventions relating to delayed age at first pregnancy, optimising inter‐pregnancy intervals, periconception folic acid, and periconception iron‐folic acid supplementation on maternal, pregnancy, birth and child outcomes. Search Methods Numerous electronic databases (e.g., CINAHL, ERIC) and databases of selected development agencies or research firms were systematically searched for all available years up to July 2019. In addition, we searched the reference lists of relevant articles and reviews, and asked experts in the area about ongoing and unpublished studies. Selection Criteria Primary studies, including large‐scale programme evaluations that assessed the effectiveness of interventions using randomised controlled trials (RCTs) or quasi‐experimental designs (natural experiments, controlled before‐after studies, regression discontinuity designs, interrupted time series [ITS]), that targeted women of reproductive age (i.e., 10–49 years) during the pre‐ and periconceptional period in LMICs were included. Interventions were compared against no intervention, standard of care or placebo. Data Collection and Analysis Two or more review authors independently reviewed searches, selected studies for inclusion or exclusion, extracted data and assessed risk of bias. We used random‐effects model to conduct meta‐analyses, given the diverse contexts, participants, and interventions, and separate meta‐analyses for the same outcome was performed with different study designs (ITS, RCTs and controlled before after studies). For each comparison, the findings were descriptively summarised in text which included detailing the contextual factors (e.g., setting) to assess their impact on the implementation and effectiveness of each intervention. Main Results We included a total of 43 studies; two of these were included in both delaying pregnancy and optimising interpregnancy intervals resulting in 26 studies for delaying the age at first pregnancy (14 RCTs, 12 quasi‐experimental), four for optimising interpregnancy intervals (one RCT, three quasi‐experimental), five on periconceptional folic acid supplementation (two RCTs, three quasi‐experimental), and 10 on periconceptional iron‐folic acid supplementation (nine RCTs, one quasi‐experimental). Geographically, studies were predominantly conducted across Africa and Asia, with few studies from North and Central America and took place in a combination of settings including community, schools and clinical. The education on sexual health and contraception interventions to delay the age at first pregnancy may make little or no difference on risk of unintended pregnancy (risk ratio [RR], 0.42; 95% confidence internal [CI], 0.07–3.26; two studies, =490; random‐effect; χ 2 p .009; I 2 = 85%; low certainty of evidence using GRADE assessment), however, it significantly improved the use of condom (ever) (RR, 1.54; 95% CI, 1.08–2.20; six studies, n = 1604; random‐effect, heterogeneity: χ 2 p .004; I 2 = 71%). Education on sexual health and and provision of contraceptive along with involvement of male partneron optimising interpregnancy intervals probably makes little or no difference on the risk of unintended pregnancies when compared to education on sexual health only (RR, 0.32; 95% CI, 0.01–7.45; one study, n = 45; moderate certainty of evidence using GRADE assessments). However, education on sexual health and contraception intervention alone or with provision of contraceptive showed a significant improvement in the uptake of contraceptive method. We are uncertain whether periconceptional folic acid supplementation reduces the incidence of neural tube defects (NTDs) (RR, 0.53; 95% CI, 0.41–0.77; two studies, n = 248,056; random‐effect; heterogeneity: χ 2 p .36; I 2 = 0%; very low certainty of evidence using GRADE assessment). We are uncertain whether preconception iron‐folic acid supplementation reduces anaemia (RR, 0.66; 95% CI, 0.53–0.81; six studies; n = 3430, random‐effect; heterogeneity: χ 2 p < .001; I 2 = 88%; very low certainty of evidence using GRADE assessment) even when supplemented weekly (RR, 0.70; 95% CI, 0.55–0.88; six studies; n = 2661; random‐effect; heterogeneity: χ 2 p < .001; I 2 = 88%; very low certainty of evidence using GRADE assessments),and in school set‐ups (RR, 0.66; 95% CI, 0.51–0.86; four studies; n = 3005; random‐effect; heterogeneity: χ 2 p < .0001; I 2 = 87%; very low certainty of evidence using GRADE assessment). Data on adverse effects were reported on in five studies for iron‐folic acid, with the main complaint relating to gastrointestinal side effects. The quality of evidence across the interventions of interest was variable (ranging from very low to moderate) which may be attributed to the different study designs included in this review. Concerning risk of bias, the most common concerns were related to blinding of participants and personnel (performance bias) and whether there were similar baseline characteristic across intervention and comparison groups. Authors' Conclusions There is evidence that education on sexual health and contraception interventions can improve contraceptive use and knowledge related to sexual health, this review also provides further support for the use of folic acid in pregnancy to reduce NTDs, and notes that weekly regimes of IFA are most effective in reducing anaemia. However the certainty of the evidence was very low and therefore more robust trials and research is required, including ensuring consistency for reporting unplanned pregnancies, and further studies to determine which intervention settings (school, community, clinic) are most effective. Although this review demonstrates promising findings, more robust evidence from RCTs are required from LMICs to further support the evidence.